Magnetic compression anastomosis for non-anastomotic stenosis of the proximal jejunum after total gastrectomy with Roux-en-Y reconstruction: a case report - Teppei Kamada; Hironori Ohdaira; Hideyuki Takeuchi; Junji Takahashi; Rui Marukuchi; Norihiko Suzuki; Satoshi Narihiro; Sojun Hoshimoto; Masashi Yoshida; Eigoro Yamanouchi; Yutaka Suzuki (Surgical Case Reports)
Abstract Background Postoperative non-anastomotic stenosis of the proximal jejunum after total gastrectomy with Roux-en-Y reconstruction is a rare complication. If endoscopic balloon dilation proves ineffective, patients need re-operation under general anesthesia and experience a high rate of postoperative complications. Magnetic compression anastomosis is a nonsurgical procedure that can create an anastomosis similar to that obtained through surgery. We report a case in which magnetic compression anastomosis was successfully performed to avoid re-operation for non-anastomotic stenosis of the proximal jejunum after total gastrectomy with Roux-en-Y reconstruction. Case presentation A 70-year-old woman was admitted to our hospital for treatment of non-anastomotic stenosis of the proximal jejunum. Open total gastrectomy and Roux-en-Y reconstruction were performed 2 years previously for advanced gastric cancer at another hospital. She complained of anorexia and obstructed passage of food. No recurrence of gastric cancer was identified. Esophagogastroduodenoscopy showed circumferential membranous stenosis of the jejunum 3 cm distal to the esophago-jejunal anastomosis. Endoscopic balloon dilation was performed three times, but proved ineffective. Magnetic compression anastomosis was planned because the stenosis existed near the esophago-jejunal anastomosis and re-operation was a highly invasive procedure requiring intrathoracic anastomosis. Endoscopic balloon dilation preceded placement of the parent magnet on the anal side of the stenosis. Confirming the improvement of stenosis, the parent magnet was placed on the anal side of the stenosis during esophagogastroduodenoscopy. The parent magnet attached to nylon thread was fixed to the cheek to prevent magnet migration. A week after placing the parent magnet, restenosis was confirmed and the daughter magnet was placed via nylon thread on the oral side of the stenosis. The two magnets were adsorbed in the end-to-end direction across the stenosis. Magnets adsorbed in the end-to-end direction moved to the anal side 11 days after placement. Wide anastomosis was confirmed by esophagogastroduodenoscopy. Endoscopic balloon dilation was regularly performed to prevent restenosis after magnetic compression anastomosis. No complications were observed postoperatively. The patient was able to eat normally and successfully reintegrated into society. Conclusions Magnetic compression anastomosis could be a feasible procedure to avoid surgery for non-anastomotic stenosis of the proximal jejunum after gastrectomy with Roux-en-Y reconstruction.